2022
DOI: 10.5888/pcd19.220066
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Access and Use Among Adults With and Without Vision Impairment: Behavioral Risk Factor Surveillance System, 2018

Abstract: What is already known on this topic? Adults aged 40 years or older with impaired vision reported having more problems related to cost of health care and availability of insurance coverage according to pooled 2002-2004 data from the Medical Expenditure Panel Survey.What is added by this report? Adults aged 18 years or older with vision impairment reported lower access to and use of health care than those without, according to the 2018 Behavioral Risk Factor Surveillance System survey.What are the implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The association of coverage gaps with unmet vision care needs was previously described in a pediatric population and may be explained by the need to find different clinicians who accept a new type of coverage, switching to plans with limited or no vision coverage, or contemporaneous social stressors (such as job loss) that disrupt access to care. As previously reported, US adults with a history of visual impairment are twice as likely to report medical costs as a barrier to vision care than adults without a visual impairment and are less likely to be covered by health insurance . Together with our data, these findings reveal the risk of a self-reinforcing cycle where socioeconomic disadvantage coincides with visual impairment and limits its effective treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association of coverage gaps with unmet vision care needs was previously described in a pediatric population and may be explained by the need to find different clinicians who accept a new type of coverage, switching to plans with limited or no vision coverage, or contemporaneous social stressors (such as job loss) that disrupt access to care. As previously reported, US adults with a history of visual impairment are twice as likely to report medical costs as a barrier to vision care than adults without a visual impairment and are less likely to be covered by health insurance . Together with our data, these findings reveal the risk of a self-reinforcing cycle where socioeconomic disadvantage coincides with visual impairment and limits its effective treatment.…”
Section: Discussionsupporting
confidence: 87%
“…As previously reported, US adults with a history of visual impairment are twice as likely to report medical costs as a barrier to vision c are than adults without a visual impairment 2 and are less likely to be covered by health insurance. 8 Together with our data, these findings reveal the risk of a self-reinforcing cycle where socioeconomic disadvantage coincides with visual impairment and limits its effective treatment.…”
Section: Discussionsupporting
confidence: 75%
“…These results are aligned with the findings from a cross-sectional analysis of the 2018 Behavioral Risk Factor Surveillance System by Cheng et al, who also noted that adults with VI had lower access to health care compared with those without VI, specifically with a lower prevalence of having medical insurance coverage (81% vs 88%) and a higher prevalence of having an unmet health need due to cost (29% vs 13%). Although their study did not analyze the impact of VI on digital health technology and nonhealth use, their findings highlight how cost may significantly hinder accessibility in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Access to digital technology is the first step in recognizing the potential inequalities that exist within telehealth between older adults with and without VI. Previous literature on VI and access to digital technology has been limited; instead, studies have focused on other consequences of VI, such as health care access 14 or tasks of everyday life. 15 Thus, the aim of this study was to identify discrepancies in digital technology access for older adults with VI compared with peers without VI using national data.…”
mentioning
confidence: 99%
“…Previous studies have confirmed that VI, combined with chronic conditions, influences patients’ health status and quality of life significantly more than one condition alone [ 9 , 50 ]. Additionally, studies have suggested that patients with VI have less access to healthcare than those without VI [ 51 , 52 ]. Therefore, for patients who have both VI and systemic conditions, especially multimorbidity, clinicians should pay more attention to their healthcare services to improve their physical status.…”
Section: Discussionmentioning
confidence: 99%